The study of sintering behavior of stainless steel 17-4PH-stainless steel 316L for two materials powders injection molding (2C-PIM) process / Najlaa Nazihah Mas’ood...[et al.] - Mas’ood, Najlaa Nazihah; Sulong, Abu Bakar; Muhamad, Norhamidi; Mohd Foudzi, Farhana; Mohd Salleh, Farrahshaida (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Two materials Powder Injection Molding (2C-PIM) is a recently developed method to manufacture functionally graded components. This study is focused on determining the suitability of two materials combined via experimental PIM technique by the sintering and microstructural evaluations. In addition, the shrinkage behavior between the two materials is also observed. The materials in 2C-PIM are said to be compatible with each other in terms of metallurgical bonding and responsive during the sintering process. The materials are stainless steels 17-4PH and 316L with palm stearin and polyethylene as the binders. It has been found that the difference sintering shrinkage for both materials is not significant due to the coefficient thermal expansion (CTE) between the two materials are quite similar. Therefore stainless steels 17-4PH and 316L can be combined successfully via the 2C-PIM technique.